Journal of applied farm economics (Purdue University Press, 2017)
Subjects include but are not limited to: animal and crop production, risk management, risk aversion, animal welfare, sustainability, precision farming, portfolio analysis, estate planning, succession planning, farmland values, land tenure and rental, strategy, growth, budgeting, technology, efficiency and productivity, cost of capital, margin hedging,